Cardiovascular and metabolic disease in the liver transplant recipient. (June 2020) - Kim, Nathan G.; Sharma, Avneesh; Saab, Sammy
Abstract: Liver transplantation has led to great improvements in long-term survival in patients with decompensated liver disease and hepatocellular carcinoma. Cardiovascular disease is the leading cause of non-graft-related deaths and has increased prevalence in liver allograft recipients. This is partly secondary to higher post-transplant rates of metabolic risk factors—notably obesity, hypertension, dyslipidemia, and diabetes mellitus, which comprise metabolic syndrome. Post-transplantation metabolic syndrome is expected to be a growing factor in morbidity and mortality as transplant candidates trend older, the rates of metabolic risk factors in the general population increase, non-alcoholic steatohepatitis grows disproportionally as an indication for transplantation, and post-transplantation survival lengthens. This review discusses the incidence and contributory factors for post-transplant increases in metabolic disease, as well as the burden of cardiovascular disease in the liver allograft recipient. Patients with pre-transplant diabetes or obesity are at particularly high risk for post-transplant metabolic syndrome, and would likely benefit from closer surveillance and more aggressive medical management of risk factors. In metabolic disease resistant to initial medical therapies, tailoring of immunosuppressive regimens may further assist in minimizing long-term cardiovascular disease, although this must be done with caution to avoid worsening the risk of graft failure.